The impact of adding community-based distribution of oral contraceptives and condoms to a cluster randomized primary health care intervention in rural Tanzania - Mallory C. Sheff; Elizabeth F. Jackson; Almamy M. Kanté; Asinath Rusibamayila; James F. Phillips (BMC, 2019)
Abstract Background Efforts to expand access to family planning in rural Africa often focus on the deployment of community health agents (CHAs). Methods This paper reports on results of the impact of a randomized cluster trial of CHA deployment on contraceptive uptake among 3078 baseline and 2551 endline women of reproductive age residing in 50 intervention and 51 comparison villages in Tanzania. Qualitative data were collected to broaden understanding of method preference, reasons for choice, and factors that explain non-use. Results Regression difference-in-differences results show that doorstep provision of oral contraceptive pills and condoms was associated with a null effect on modern contraceptive uptake [p = 0.822; CI 0.857; 1.229]. Discussions suggest that expanding geographic access without efforts to improve spousal and social support, respect preference for injectable contraceptives, and address perceived risk of side-effects offset the benefits of adopting contraceptives provided by community-based services. Conclusions The results of this study demonstrate that increasing access to services does not necessarily catalyze contraceptive use as method choice and spousal dynamics are key components of demand for contraception. Findings attest to the importance of strategies that respond to the climate of demand. Trial registration Controlled-Trial.com ISRCTN96819844. Retrospectively registered on 29.03.2012.